Formación ética y persona: obra de arte interior - Aragón Quintero, José Ariel (Universidad Pedagógica y Tecnológica de Colombia, 2019)
To form integrally from us as educators from the full self- knowledge to be able to look more closely at the person of our students is the task that corresponds to the educator of educators of the degree in Basic Education. They are in depth and in the complexity of their being an inner work of art that is necessary to be discovered. Therefore, we must educate the whole person, not reduce it only to stock up information, if so, we are not fulfilling our essential function of educating. Students as subjects of changes and continuing transformations of realities, have as destination their realization and their happiness in the middle of their daily activity, whose stage is the world around them.